The social side of sustainable business models: An explorative analysis of the low-cost airline industry. (10th July 2019) - Rotondo, Federico; Corsi, Katia; Giovanelli, Lucia
Abstract: The concept of a sustainable business model has increasingly been used to depict business cases that, by incorporating a triple bottom line approach, seek to realize economic success through environmental and social initiatives. Nevertheless, there is a call for more empirical research on design and innovation with respect to sustainable business models, as well as on the relationship they have with firm performance. This paper focuses on the social side of sustainability and aims to explore the extent to which integrating social sustainability objectives into the business model has a positive influence on a firm's financial performance, promotes sustainable innovation and enhances the firm's ability to withstand discontinuities such as the recent financial crisis. Following a review of the existing literature, four propositions are formulated and subsequently tested through a multiple case study of four international low-cost carriers. The results have implications for theory and practice as they reveal that integrating social sustainability in the business model i) does not automatically influence financial performance, although it may have a role in the long-term financial outcomes of the firm; ii) influences the characteristics and effectiveness of sustainable innovation; iii) must be accompanied by intelligent managerial activity to be effective; and iv) does not necessarily lead to faster financial recovery in the aftermath of a discontinuity, but it does make a firm more resilient over a long-term basis. Graphical abstract: Image 1 Highlights: Social sustainability of business models does not affect short-term financial success. Social sustainability of business models influences sustainable innovation. Social sustainability of business models should be supported by management systems. Social sustainability of business models does not lead to faster financial recovery. Social sustainability of business models promotes greater social resilience.